Perbandingan Kapasitas Struktur Cermaton yang Diubah Menjadi Pile Slab Terhadap Beban Rencana - Putra, Muhammad Andika Pratama; Indianto, Andi (Indonesian Society of Applied Science, 2022)
One of the bridges on the Serpong-Balaraja Toll Road section 1a project with the longest span is the Cisadane Bridge, which will employ a PCI Girder superstructure with a length of 50.8 meters. The approach road structure for the Cisadane Bridge was originally intended to employ Cermaton with a soil pile that was 6–8 m high. However, during construction, the design of the approach road changed from Cermaton to pile slab. In order to determine which structure is the most suitable for use, it is required to assess its performance. The SAP2000 program was used to check the bearing capacity of the foundation, the settlement that took place, and the structural capacity against seismic loads as part of the evaluation that was done as a result of changes in the structural design. The study results for structural design change demonstrated that the Cermaton was not superior to the pile slab since the Cermaton's decrease, which was 11.3 mm as opposed to 1.06 mm for the pile slab, was substantially greater. For an analysis of earthquake loads using SAP2000 software, it was found that Cermaton is not strong enough to withstand earthquake loads, while the pile slab is strong enough to withstand earthquake loads because the capacity of the pile slab is still adequate.